Isolation and Preliminary Characterization of Proteinaceous Toxins with Insecticidal and Antibacterial Activities from Black Widow Spider (L. tredecimguttatus) Eggs - Qian Lei; Hai Yu; Xiaozhen Peng; Shuai Yan; Jirong Wang; Yizhong Yan; Xianchun Wang (Toxins, 2015)
The eggs of black widow spider (L. tredecimguttatus) have been demonstrated to be rich in toxic proteinaceous components. The study on such active components is of theoretical and practical importance. In the present work, using a combination of multiple biochemical and biological strategies, we isolated and characterized the proteinaceous components from the aqueous extract of the black widow spider eggs. After gel filtration of the egg extract, the resulting main protein and peptide peaks were further fractionated by ion exchange chromatography and reversed-phase high performance liquid chromatography. Two proteinaceous components, named latroeggtoxin-III and latroeggtoxin-IV, respectively, were purified to homogeneity. Latroeggtoxin-III was demonstrated to have a molecular weight of about 36 kDa. Activity analysis indicated that latroeggtoxin-III exhibited neurotoxicity against cockroaches but had no obvious effect on mice, suggesting that it is an insect-specific toxin. Latroeggtoxin-IV, with a molecular weight of 3.6 kDa, was shown to be a broad-spectrum antibacterial peptide, showing inhibitory activity against all five species of bacteria tested, with the highest activity against Staphylococcus aureus. Finally, the implications of the proteinaceous toxins in egg protection and their potential applications were analyzed and discussed.